The art of falling in love - Beam, Joe. (New York : Howard Books, 2012)
Describes the lovepath, the author's process for finding and maintaining true love.
The path to love -- The call to closeness -- The craving for caring -- Why we fall madly in love -- The stage of commitment -- The dynamics of difference -- Relationship in retreat -- The challenge of conflict -- The fulfillment of intimacy -- Learning to love anew.
Includes bibliographical references.
Keywords: Man-woman relationships; Love; Mate selection; Interpersonal relations